2015
DOI: 10.1016/j.eurpsy.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence ofDepdc7Dna Hypomethylation in Depression: a Study in Adult Twins

Abstract: Late and early stressful factors have widely been recognized to play a role in the aetiology of depression. Recent research indicates that such adverse environmental stimuli may alter gene expression in humans via epigenetic modifications. While epigenetic changes such as DNA methylation are likely involved in these processes, it is still unknown what specific genomic loci may be hyper- or hypo-methylated in depression. The association between depressive symptoms during the last 30 days (Brief Symptom Inventor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Although studies of methylation in strokes have indicated a range of changes in protein basal level [ 33 ], the targets of methylation regulation have not yet been the subject of a dedicated study. Proteins that have large basal level changes and are not miRNA targets (ACTA2 [ 34 ], C4BPA [ 35 ], CD3G [ 36 ], CENPK [ 37 ], DEPDC7 [ 38 ], FECH [ 39 ], HLA-DQA1 [ 40 ], HLA-DRB4 [ 41 ], and NKX3-1 [ 42 ]) can be potential targets of methylation regulations. Based on the specific targets of miRNA regulations and the position of the target proteins in the core networks, several potential drug targets can be selected (* in Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although studies of methylation in strokes have indicated a range of changes in protein basal level [ 33 ], the targets of methylation regulation have not yet been the subject of a dedicated study. Proteins that have large basal level changes and are not miRNA targets (ACTA2 [ 34 ], C4BPA [ 35 ], CD3G [ 36 ], CENPK [ 37 ], DEPDC7 [ 38 ], FECH [ 39 ], HLA-DQA1 [ 40 ], HLA-DRB4 [ 41 ], and NKX3-1 [ 42 ]) can be potential targets of methylation regulations. Based on the specific targets of miRNA regulations and the position of the target proteins in the core networks, several potential drug targets can be selected (* in Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A twin-based approach previously developed in our group [55] was also applied to refine the association between cg06793497 methylation and CPR. Briefly, intrapair differences for both variables of interest were computed for each twin pair; afterward, a regression model was fitted with an estimated intrapair cg06793497 methylation (Δmethylation) and intrapair CPR (ΔCPR).…”
Section: Methodsmentioning
confidence: 99%
“…Brain expression of DEPDC7 was not detectable. However, it has been suggested that DEPDC7 DNA hypomethylation may be associated with depression (Córdova-Palomera et al, 2015). The biological function of the protein encoded by the DEPDC7 (DEP domain-containing 7) gene is poorly understood.…”
Section: Ddx25 (Dead (Asp-glu-ala-asp) Box Polypeptidementioning
confidence: 99%